Pushing the boundaries of patient experience - Jason Wolf (The Beryl Institute, 2017)
This special issue is designed to push the boundaries of patient experience a little farther. Beyond just examples of applying the critical principles of patient and family centered care or even practices of patient engagement, we have been pushed to move further down the perspective of partnership, to the era of "doing with" in which healthcare now finds itself. The idea of involvement as the descriptor selected to frame this issue, was due to its broad and representative nature. It reflects all the words on involving patients mentioned above, but gets further along to participation and ownership (or activation as many now tend to use) and even beyond partnership to the intimacy involvement connotes. Involvement here gets us to the personal and emotional levels that connects someone to what they are doing and reflects the whole person connected to that experience. That represents the opportunity reflected in this issue and in pieces that have comprised Patient Experience Journal to date. Through these contributions we have realized an opportunity to invite disparate voices and introduce new ideas, to gray the edges of what people deemed patient experience to be, and to push the boundaries of what patient experience truly is.